PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN AUGMENTED REALITY TERHADAP PENINGKATAN PEMAHAMAN KONSEP IPAS SISWA KELAS V MI CIOMAS - Indra Lesmana; Mas Ramadhan, Gilang; Janatriasari, Rida; Putriyani, Uput (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by Augmented Reality (AR) on improving the understanding of Integrated Science and Social Studies (IPAS) concepts among fifth-grade students at MI Ciomas. The background of this study was the low level of students' conceptual understanding caused by teacher-centered learning and the limited use of interactive learning media. This research employed a quantitative approach using a Pre-Experimental method with a One Group Pretest–Posttest Design. The research subjects consisted of 22 fifth-grade students selected using saturated sampling. Data were collected through essay tests that had been tested for validity and reliability. The data were analyzed using descriptive statistics, normality testing, and the Paired Sample t-test. The results showed that the average pretest score was 47.41, while the average posttest score increased to 84.50 after the implementation of the Problem Based Learning model assisted by Augmented Reality. The normality test indicated that both pretest and posttest data were normally distributed. Furthermore, the Paired Sample t-test yielded a significance value (Sig. 2-tailed) of 0.000, which was lower than 0.05, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. These findings demonstrate that the implementation of the Problem Based Learning model assisted by Augmented Reality has a significant positive effect on improving students' understanding of IPAS concepts. Therefore, the integration of Problem Based Learning and Augmented Reality can serve as an innovative and effective learning strategy to enhance conceptual understanding in elementary school science education.